UPAYA MENINGKATKAN MOTIVASI DAN PRESTASI BELAJAR MATEMATIKA DENGAN MODEL PEMBELAJARAN KOOPERATIF TIPE STRUCTURED NUMBERED HEADS (SNH) SISWA KELAS X TEKNIK GAMBAR BANGUNAN (TGB) SMK NEGERI 1 SEDAYU TAHUN PELAJARAN 2013/2014 - Fajar Suryanto; Istiqomah Istiqomah (UNION: Jurnal Ilmiah Pendidikan Matematika, 2016)
The effort to improve motivation and achievement learn mathematics with model study of  cooperative learning type Structured Numbered Heads (SNH) student class the on of X Techhnique of Building Design  (TGB) SMK Negeri 1 Sedayu in year 2013/2014. The type of this research is classroom action research collaboratively. The subject of the research are students class X TGB SMK Negeri 1 Sedayu. It consist 32 students. While the object is the motivation and achievement of students learning mathematics derived from the application of model study of  cooperative learning type Structured Numbered Heads (SNH).The result shows the increase by using this model. It is indicated by an improvement in the average percentage of math learning motivation questionnaire sheet  for each cycle, the pre-cycle students' motivation  for 59.33% increase to 74,57%% in the first cycle, and increased in the second cycle be 82,68%. In addition, the average value of mathematics learning achievement of students has increased, in the pre cycle is 63,5 with the percentage of  completeness 46,90% (15 students), in the first cycle increased to 71,09 with the percentage of completeness 62,50% (20 students), while on the second cycle increased to 80,88 with the percentage of completeness 81.25% (26 students). Based on the result of the research expected to the teachers in order to be able to use the learning model on the Structured Numbered Heads (SNH) which as one of the models of learning that to be able to improve the motivation and achievement of learning mathematics.